2014
DOI: 10.1037/a0035408
|View full text |Cite
|
Sign up to set email alerts
|

The effects of staffing and training on firm productivity and profit growth before, during, and after the Great Recession.

Abstract: This study integrates research from strategy, economics, and applied psychology to examine how organizations may leverage their human resources to enhance firm performance and competitive advantage. Staffing and training are key human resource management practices used to achieve firm performance through acquiring and developing human capital resources. However, little research has examined whether and why staffing and training influence firm-level financial performance (profit) growth under different environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
243
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(263 citation statements)
references
References 140 publications
17
243
1
2
Order By: Relevance
“…Our result supports the contingent view of the resource‐based theory advocated by Datta et al () and Kim and Ployhart (), which predicts that the effectiveness of HR investment is moderated by the economic conditions of the environment. Datta et al () show that in an environment of economic growth, the positive relationship between HR investment and labor productivity is greater.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our result supports the contingent view of the resource‐based theory advocated by Datta et al () and Kim and Ployhart (), which predicts that the effectiveness of HR investment is moderated by the economic conditions of the environment. Datta et al () show that in an environment of economic growth, the positive relationship between HR investment and labor productivity is greater.…”
Section: Discussionsupporting
confidence: 89%
“…An economic crisis leads to layoffs and widespread downsizing in companies and, as a result, substantial and sudden reductions in the workforce (Kim & Ployhart, ), which have detrimental consequences for the organization. First, the departure of workers can disrupt the complex social process that fosters cooperative behavior among workers by destroying their relationship networks, which in turn can seriously damage task accomplishments and organizational learning capability (Sahdev, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Labor productivity, defined as the ratio of firm outputs to labor inputs (Samuelson & Nordhaus, 1989), is a critical indicator of workforce performance (Datta, Guthrie, & Wright, 2005;Kim & Ployhart, 2014). In light of our agency predictions, we expect family firms to exhibit lower labor productivity than nonfamily firms.…”
Section: Labor Productivitymentioning
confidence: 99%
“…For example, Guest et al (2013) confirm the association between HRM and performances but fail to show that HRM leads to high performance. On the other hand, using 359 firms with over 12 years of longitudinal firm-level profit data, Kim and Ployhart (2014) suggest that selective staffing and internal training directly and interactively influence firm profit growth through their effect on labour productivity. Similarly, by using panel data to examine the potential casual order between HPWP systems and firm performance in small businesses, both Sheehan (2014) and Razouk (2011) find a positive significant relationship between HRM and performance, even after controlling for the past performance.…”
Section: That Is '(Hrm) Responds Accurately and Effectively To The Ormentioning
confidence: 99%
“…Five studies reported both operational and financial performance measures (e.g. Kim and Ployhart, 2014;Sheehan, 2014).…”
mentioning
confidence: 99%